Postharvest Ozone Fumigation of Grapes (cv Sangiovese) Differently Affects Volatile Organic Compounds and Polyphenol Profiles of Berries and Wine - Margherita Modesti; Stefano Brizzolara; Roberto Forniti; Brunella Ceccantoni; Andrea Bellincontro; Cesare Catelli; Fabio Mencarelli; Pietro Tonutti (Australian Journal of Grape and Wine Research)
Consumers are more and more oriented towards the purchase of safer food and beverages, which is pushing the wine sector to find alternatives to the use of sulfur dioxide. Ozone (O3) is already applied in the wine industry to produce sulfur dioxide-free wines through the patented method Purovino®. The aim of this two-year study was that of evaluating whether the postharvest treatment of grapes with ozone affects volatile organic compounds (VOCs) and polyphenol profile in berries, and in turn, wine composition. Grape bunches (Vitis vinifera L.) of cv Sangiovese were fumigated overnight with gaseous ozone (max 20 g·h−1 with 6% w.w−1 of ozone) in a cold room at 4°C (±0.5). After treatment, grapes were processed into wine. In grapes, ozone treatments increased total polyphenol and flavonoid content and upregulated specific genes (phenylalanine ammonia lyase, VvPAL, flavanol synthase 1, and VvFLS1) involved in polyphenol biosynthesis. Wine obtained from ozone-treated grapes had higher flavanol content than the control. Fumigation only slightly affected the different VOC classes of grapes and wine, including aroma compounds derived from the lipoxygenase (LOX) pathway. Although a season-dependent effect was observed, results showed that postharvest ozone treatments applied to avoid the use of sulfur dioxide introduced limited but, in general, positive modifications to grape and wine composition. This information provides assurance to winemakers that the maintenance of wine quality and typicity will be guaranteed when using ozone treatments.